Influence of salt works’ hyper-saline waste-brine on distribution of mangrove crabs (Decapoda) along the Gongoni-Kurawa intertidal area, North Coast Kenya - S. K. , Mumbah; Manyala , J. O.; Njiru , J.M; B. , Fulanda; A. B. , Kaunda (African Journal of Education,Science and Technology (AJEST), 2018)
The impact of the discharged hyper-saline waste-brine waters on the mangrove crabs along the intertidal habitats bordering two of the biggest salt works; Krystalline and Kurawa salt industries was investigated in this study. Sampling was done during both spring and neap season in the year 2015 between the month of February to June using 1m2 quadrats, and crabs collected from the quadrats used to estimate the densities. A total of 34 mangrove crab species were recorded, with abundances significantly higher (p>0.05) within the inlets’ habitats as compared to the outlets (discharge-point) habitats. Six species were most dominant and occurred in all of the transect samples and they were Machrophthalmus grandidieri, Uca chlorophthalmus, Terebralia palustris, Machrophthalmus latreillei, Uca tetragonon and Amaea acuminata. Higher species diversity and evenness were recorded in inlet habitats at Kurawa compared to the outlets. The inlet habitats reported higher Maximum Shannon-Wiener diversity, whereas outlets recorded lower diversity, with Marereni recording considerably lower Hmax, at 0.95. Species distribution showed a significant reduction of the genera Uca and M. grandidieri (p<0.05) at Marereni outlet habitats, but an increase in U. vocans at the inlet habitats. Similarly, there was a higher abundance of genera Uca, M. ovalina, M. grandidieri, M. latreillei, Amaea acuminata and Cerithidea decollata (p<0.05) during the spring tide period while the abundances of U. vocans dropped during the same period. This asymmetric distribution between inlets and outlets was explained by significant variations in salinity as well as site specific salinity gradients at the two study sites; Marereni and Kurawa in north coast, Kenya. Suggestions for improving salt production and quality while minimizing adverse environmental effects were recommended.